2011
DOI: 10.4322/rbcv.2014.123
|View full text |Cite
|
Sign up to set email alerts
|

Biópsias endometriais de éguas: avaliação imuno-histoquímica e definição de protocolo

Abstract: A imuno-histoquímica é uma importante técnica de diagnóstico e na Medicina Veterinária ainda se faz necessário a realização de testes para padronização dos anticorpos a serem utilizados. O objetivo deste estudo foi avaliar e descrever a imunomarcação de anticorpos anticomponentes celulares e da matriz extracelular humana, como o antivimentina, antidesmina, anti-PCNA, anti-CK20 e antialfa actina de músculo liso, após padronizações na técnica, em amostras de biópsia endometrial de égua. Duas amostras endometriai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Despite the difficulty and necessary care in interpreting PCNA immunostainings (clone PC10), as described by Yu and Filipe (1993) and Martins et al (2011), the cell proliferation distribution pattern observed in the present work was very similar to that described by Gerstenberg, Allen and Stewart (1999). However, Gerstenberg, Allen and Stewart (1999) have assessed the cell proliferation patterns in equine endometrium during the estrous and seasonal cycles, by using the Ki67 immunomarker in frozen sections.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Despite the difficulty and necessary care in interpreting PCNA immunostainings (clone PC10), as described by Yu and Filipe (1993) and Martins et al (2011), the cell proliferation distribution pattern observed in the present work was very similar to that described by Gerstenberg, Allen and Stewart (1999). However, Gerstenberg, Allen and Stewart (1999) have assessed the cell proliferation patterns in equine endometrium during the estrous and seasonal cycles, by using the Ki67 immunomarker in frozen sections.…”
Section: Discussionmentioning
confidence: 68%
“…Initially described by Miyachi, Fritzler and Tan (1978), the proliferating cell nuclear antigen (PCNA) is an auxiliary protein of DNA polymerase d and e, the enzymes that are needed for DNA synthesis (KELMAN, 1997). Expression of PCNA increases during G1 phase of cell cycle, reaches its expression peak in the S phase, and declines during the G2\M phase, and its immunomarking characteristics allow the identification of cells in the different phases of the cycle (WOOD; SHIVIJ, 1997;MARTINS et al, 2011).…”
Section: Introductionmentioning
confidence: 99%